Implementation of Village Management Information System for Monitoring and Evaluation of Pangkul Village Development Program - Zaiyanah Putriyani; Andi Christian; Iwan Setiawan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Pangkul Village is optimizing monitoring and evaluation of development programs through the implementation of a new information system. This system was developed using agile methods to adapt to rapidly changing needs. By implementing agile methods in monitoring and evaluating village development programs, it is hoped that a more adaptive and results-oriented process can be created that is beneficial to the community. This activity aims to identify progress, challenges, and impacts of development programs, as well as ensure community participation in the village development process. The evaluation results show the development of village government performance in planning and implementation, as well as the identification of relevant performance indicators for continuous improvement